Linear discriminant analysis in network traffic modeling - ZHANG Bing-yi; BIAN Yu-lan; ZHANG Hong-ke; SUN Ya-min (Tongxin xuebao)
It was not easy to give an accurate judgment of whether the traffic model fitting the actual traffic. The common method was to compare the Hurst parameter, data histogram and autocorrelation function. The method of comparing Hurst parameter could’t give exact results and judgment. The method of comparing data histogram and autocorrelation could only give a qualitative judgment. Based on linear discriminant analysis a arithmetic was proposed. Utilizing this arithmetic the data in the sets of different traffic model and in NS was analyzed. The results are accurate. Compared with traditional method this arithmetic is useful and can conveniently give an accurate judgment for complex network traffic trace.